Drying–rewetting cycles and γ-irradiation effects on enzyme activities of distinct layers from a Quercus ilex L. litter - Alarcón-Gutiérrez, Enrique; Floch, Carine; Ziarelli, Fabio; Augur, Christopher; Criquet, Stéven (Soil Biology and Biochemistry, 2010)
In a Mediterranean climate, water stress is one of the principal constraints on proper forest ecosystem functioning. Drought influences rates of organic matter degradation by affecting microbial growth and enzyme activities. The objectives of this study were: (i) to evaluate the effect of repeated dryingerewetting cycles on cellulase, alkaline phosphatase and fluorescein diacetate (FDA) hydrolase activities of three distinct Quercus ilex L. litter layers, and (ii) to investigate the effect of these cycles on γ-irradiated litters in order to distinguish the abiotic influence on the fluctuations observed. Results, for all three layers, showed high correlations between litter water content and enzyme activities. Under mesocosm conditions, and using non-sterilized litter samples, cellulase, alkaline phosphatase, and FDA activities significantly decreased or increased during drying or rewetting cycles respectively. Significant differences were also found when evaluating the effect of litter depth on enzyme activities, the intermediate depth (OLv layer) generally being the most active. For γ-sterilized samples, FDA activity still fluctuated with dryingerewetting cycles. Assays showed that pre-humidification of γ-irradiated litter increased FDA activity two-fold in the first 30 min. All these results have shown that, following dryingerewetting cycles, some of the fluctuations occur independently of microbial growth, suggesting abiotic interactions, such as desorption, in combination with both solvatation status and conformational changes of enzymes.
Keywords: abiotic fluctuations; Drying-rewetting; Enzyme activities; Moisture; γ-Irradiation

Refining vegetation simulation models: From plant functional types to bioclimatic affinity groups of plants - Laurent, J.-M.; Bar-Hen, A.; François, L.; Ghislain, M.; Cheddadi, R. (Journal of Vegetation Science, 2004)
Question: How to refine simulations based on a global vegetation model in order to apply it to regional scale? Location: Europe from 35° N to 71° N and 25° W to 70° E. Methods: Geographical ranges of European plants were georeferenced and used with monthly mean climatic data (diurnal temperature ranges, ground frost frequencies, precipitation, relative humidity, rain frequencies, amount of sunshine hours and temperature) and growing degree days to infer climatic boundaries for 320 taxa. We performed a discriminant analysis to define their potential geographic ranges. Hierarchical clustering was computed on potential ranges. Results: Clustering provided 25 Bioclimatic Affinity Groups (BAG) of plants consisting of 13 tree, seven shrub and five herb groups. These B AGs are characterized by different geographical ranges and climatic tolerances and requirements. Conclusion: The use of monthly data instead of annual values improved the prediction of potential distribution ranges and highlighted the importance of climate seasonality for defining the plant groups with accuracy. The B AGs are detailed enough to provide finer reconstructions and simulations of the vegetation at the regional scale.
The following values have no corresponding Zotero field: publisher: Blackwell Publishing Ltd
Keywords: CARAIB; Discriminant analysis; Hierarchical clusteranalysis; Moisture; pollen; Seasonality; Temperature; Vegetation distribution